2002
DOI: 10.1001/archpsyc.59.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Smaller Left Posterior Superior Temporal Gyrus Volume on Magnetic Resonance Imaging and Smaller Left Temporal P300 Amplitude in First-Episode Schizophrenia

Abstract: Background:In chronic schizophrenia, the P300 is broadly reduced and shows a localized left temporal deficit specifically associated with reduced gray matter volume of the left posterior superior temporal gyrus (STG). In first-episode patients, a similar left temporal P300 deficit is present in schizophrenia, but not in affective psychosis. The present study investigated whether the left temporal P300-left posterior STG volume association is selectively present in first-episode schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
113
5
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 53 publications
16
113
5
3
Order By: Relevance
“…The substantial reduction in midline P300 amplitude in FEP-S patients relative to normal controls confirms previous findings (e.g., Salisbury et al 1998;McCarley et al 2002). However, this reduction appears to be of greater magnitude in the present study: P300 peak amplitudes in FEP-S patients were about half of that found by Salisbury et al (1998), and one third of that found by McCarley et al (2002).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The substantial reduction in midline P300 amplitude in FEP-S patients relative to normal controls confirms previous findings (e.g., Salisbury et al 1998;McCarley et al 2002). However, this reduction appears to be of greater magnitude in the present study: P300 peak amplitudes in FEP-S patients were about half of that found by Salisbury et al (1998), and one third of that found by McCarley et al (2002).…”
Section: Discussionsupporting
confidence: 89%
“…However, this reduction appears to be of greater magnitude in the present study: P300 peak amplitudes in FEP-S patients were about half of that found by Salisbury et al (1998), and one third of that found by McCarley et al (2002). In addition to the differences between the experimental protocols used, a possible explanation for this discrepancy is medication.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations